O uso de tecnologias na formação continuada de professores de matemática, no âmbito da educação a distância, em uma diretoria de ensino no Estado de São Paulo - Araújo, Daniel Oliveira de (Universidade Federal de São Carlos, 2017)
The present study had as main objective to develop an interactive virtual environment capable of advising the teacher in his pedagogical practices. From this environment we extracted the data that were analyzed and discussed, based on the reports of the students involved. In the course of this work three considerable procedures were carried out: the creation of Blog www.belelite.blogspot.com.br, the management of information that fed the blog and were topics of discussions between the students and the teacher and finally the preparation of The challenge of Virtual Knowledge, a workshop material to be held at the Technical Workshops promoted by the Teaching Board of the city of São Roque in SãoPaulo.
Keywords: Educação à distância; Ambiente virtual de aprendizagem; Formação continuada de professores de matemática; Blogs; Ensino superior; Distance education; Virtual learning environment; Continuing education of mathematics teachers; Higher education; CIENCIAS EXATAS E DA TERRA::MATEMATICA